2021
DOI: 10.1002/chem.202004525
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Noncovalent Interactions in Azide–Pnictogen, –Chalcogen, and –Halogen Contacts

Abstract: The noncovalent interactions between azides and oxygen‐containing moieties are investigated through a computational study based on experimental findings. The targeted synthesis of organic compounds with close intramolecular azide–oxygen contacts yielded six new representatives, for which X‐ray structures were determined. Two of those compounds were investigated with respect to their potential conformations in the gas phase and a possible significantly shorter azide–oxygen contact. Furthermore, a set of 44 high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 102 publications
4
29
1
Order By: Relevance
“…The bond dissociation energy of these interactions from the Espinosa correlation [26] is calculated to be between 2.38 kcal mol −1 to 4.17 kcal mol −1 . The closed‐shell nature and energetics agree well with the previous studies, that this interaction arise mainly due to London dispersion and electrostatic forces between azide‐donor pairs [13] …”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…The bond dissociation energy of these interactions from the Espinosa correlation [26] is calculated to be between 2.38 kcal mol −1 to 4.17 kcal mol −1 . The closed‐shell nature and energetics agree well with the previous studies, that this interaction arise mainly due to London dispersion and electrostatic forces between azide‐donor pairs [13] …”
Section: Figuresupporting
confidence: 90%
“…Apart from the common and well‐studied NCIs such as various types of hydrogen bonding, [7] halogen bonding, [8] chalcogen bonding, π‐π stacking, dipole‐dipole interaction, [9] several other interactions have come to light recently [10, 11] . Our recent study on azide‐chalcogen interaction suggested that it involves both London dispersion interactions [12] and electrostatic contributions [13] . However, for any new NCI to be used for designs with confidence, experimental validation of its influence and relevance in different molecular systems is essential.…”
Section: Figurementioning
confidence: 99%
“…In conclusion, CREST is a powerful tool for simulations of molecules up to a few hundred atoms and will potentially find wide spread application in computational chemistry. Since first being published, the program has already been applied for a diverse number of projects, e.g., the large scale conformer generation of organometallic compounds, 183,590 protein side chain conformational sampling, 591 gas docking in metal-organic frameworks (MOF), 444 input generation of machine-learning approaches, 414 and various other mechanistic, 592-594 conceptual, [595][596][597][598] and spectroscopic studies. 22,476,[599][600][601] In Part III, a recent extension to the CREST code was presented and discussed linking the conformational low-energy chemical space to statistical thermodynamics.…”
Section: Final Summary and Conclusionmentioning
confidence: 99%
“…[26] Theb ond dissociation energy of these interactions from the Espinosa correlation [26] is calculated to be between 2.38 kcal mol À1 to 4.17 kcal mol À1 .T he closed-shell nature and energetics agree well with the previous studies, that this interaction arise mainly due to London dispersion and electrostatic forces between azide-donor pairs. [13] Topological analysis for this particular interaction has been quite challenging because of certain abnormal trends. Forinstance,weobserved that structure 33 (Figure S2), which did not show BCP in its crystal structure geometry,shows an azide-oxygen interaction in its geometry-optimized structure.…”
mentioning
confidence: 99%
“…[10,11] Our recent study on azide-chalcogen interaction suggested that it involves both London dispersion interactions [12] and electrostatic contributions. [13] However,f or any new NCI to be used for designs with confidence,e xperimental validation of its influence and relevance in different molecular systems is essential. Here we report the experimental proof for the role of azide•••oxygen interaction in dictating the conformation of different classes of molecules.…”
mentioning
confidence: 99%